Dispersion analysis of arbitrarily cut orthorhombic crystals - Hoefer, Sonja; Ivanovski, Vladimir; Uecker, Reinhard; Kwasniewski, Albert; Popp, Juergen; Mayerhoefer, Thomas G. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2017)
We developed a measurement and evaluation scheme to perform dispersion analysis on arbitrarily cut orthorhombic crystals based on the schemes developed for triclinic and uniaxial crystals. As byproduct of dispersion analysis the orientations of the crystal axes are found. In contrast to the spectra of arbitrarily cut uniaxial crystals, where the fit routine has to separate two independent principal spectra, the spectra of arbitrarily cut orthorhombic crystals are a combination of three independent spectra and the evaluation scheme gets more complex. Dispersion analysis is exemplary performed on two different crystals, which show different spectral features and different levels of difficulties to evaluate. Neodymium gallate (NdGaO3) has broad overlapping reflections bands while topaz (Al2SiO4 [F, OH]2) has a quite high total number of infrared active bands.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Arbitrarily cut crystals; Crystal orientation; Dispersion analysis; Orthorhombic crystals